Can we prevent Parkinson''s disease with n-3 polyunsaturated fatty acids?. (April 2008) - Calon, Fréédééric; Cicchetti, Francesca
It is increasingly clear that nongenetic elements play a crucial role in the pathogenesis of Parkinson''s disease (PD), yet no modifiable environmental risk factor has been clearly identified. Recent work in animal models of PD supports the contention that n-3 polyunsaturated fatty acids (PUFA) found in fatty fish are neuroprotective in PD. Moreover, a few epidemiological reports suggest that a high intake of fish (and n-3 PUFA) is associated with a lower risk of developing PD. The question remains whether docosahexenoic or eicosapentenoic acid is the brain n-3 PUFA responsible for the observed neuroprotective effect. Despite these encouraging data, the development of n-3 PUFA as drugs is hindered by the fact that they are nonpatentable compounds, at least in their natural form. Nevertheless, owing to their favorable safety profile, it should be a high priority to pursue preclinical and clinical studies on the nutraceutical properties of n-3 PUFA in PD.